Penerapan Model The Big Six untuk Meningkatkan Kemampuan Literasi Digital Siswa MAS AL-ISHLAH AL-AZIZYAH - Deni, Rosica; Rizal, Syamsul; Azzarkasyi, Muhammad (Journal of Technology and Literacy in Education, 2024)
The big six model is a model for solving information problems through a library approach and improving various information literacy skills. This research aims to determine the effectiveness and improvement of students’ digital information literacy skills through the application of the big six model. The method used in this approach is a cross-sectional survey method. The research sample of all class X students in the first semester of the 2024/2025 academic year was 20 students. The instruments used in this research are observation guidelines and questionnaires related to the big six model and digital literacy skills. The results of the research show that: (1) On average, students’ digital literacy skills are classified as sufficient, namely with a score of 67, while in the final observation, students’ digital literacy skills are classified as good, namely with a score of 81.2. (2) The effectiveness of the big six model can be seen based on the average score obtained from the students’ questionnaire on the big six model of 88% with the criteria of strongly agree, while the digital literacy skills questionnaire obtained an average of 89.5% with the criteria of strongly agree